Rating Student Performance. - Pattillo, James W. (The Accounting Review, 1966)
The article focuses on the evaluation of student performances. Some schools make student evaluations known to the student body, faculty, or university administration. This usually takes the form of a booklet and may be published for everyone, or only for faculty use. Its purpose is to point out the bad teachers. Faculty, for obvious reasons, have mixed sentiments about such a publication. But, in general it is considered to upgrade the quality level of the faculty by focusing attention upon those doing the worst job of instruction. A complicating factor is that once the student completes the course, it is hard to recall in any detail his performance other than the final course grade. Except for the few outstanding students, it is hard to give opinions about performance and qualities when inquiries are made. One means of having a permanent record of student evaluation is by using a rating sheet such as that developed at the University of Southern California. The questionnaire covers three basic areas, the student's relationship to class activities, personal qualities, and suitability for employment in a certified public accountants firm.